Properties and degradability of paper sludge filled polypropylene/ethylene propylene diene terpolymer composites - Ismail Ibrahim (School of Materials Engineering, 2011)
The primary objective of the study is to determine the feasibility of paper sludgein polypropylene (PP)/ethylene propylene diene terpolymer (EPDM) with aim to develop thermoplastic elastomer composites. In order to obtain a basic understanding of the paper sludge as filler into PP/EPDM blends on the degradation testing such as biodegrable, hygrothermal, thermo-oxidative ageing, thermogravimetry analysis and ultra violet weathering properties of composites were studied.